Cardiac involvement in familial Mediterranean fever - A. Yu. Gasparyan; A. H. Petrosyan (Кардиоваскулярная терапия и профилактика, 2007)
The paper deals with contemporary issues of cardiac involvement at various stages of periodic disease (familial Mediterranean fever). It is supposed that inflammation during acute attacks, in between attacks and in case of amyloidosis development is the main pathologic factor leading to functional and organic heart disturbances in this disease. Shifts of some immunological parameters, along with activation of sympatho!adrenal and other systems and organs, are considered as pathogenic factors predisposing to exhaustion of heart functional reserves. Based on the pathomorphological data, it is possible to claim that myocardial dysfunction, due to microvascular pathology and amyloid sedimentation, is a characteristic feature of the disease, though involvement of other heart structures is not excluded. The main directions for cardiac involvement diagnostics are described and comparatively analyzed.